2019
DOI: 10.1111/ap.12406
|View full text |Cite
|
Sign up to set email alerts
|

The essential role of mental imagery in cognitive behaviour therapy: What is old is new again

Abstract: Objective: The aim of this review is to highlight the important role of mental imagery in contemporary cognitive behaviour therapy (CBT). Method: In this narrative review, we define mental imagery based on cognitive science research, present the rationale for the incorporation of mental imagery within CBT, and outline four key applications of mental imagery within CBT practice (i.e., imagery-enhanced thought records, imagery-enhanced behavioural experiments, imaginal facilitation of behaviour change, and image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
(60 reference statements)
2
13
0
3
Order By: Relevance
“…These authors found that higher levels of anxiety were associated with obsessive images experienced in the first person. Saulsman et al (2019) have underscored the important role of mental imagery in contemporary cognitive behavioral therapy.…”
Section: Introductionmentioning
confidence: 99%
“…These authors found that higher levels of anxiety were associated with obsessive images experienced in the first person. Saulsman et al (2019) have underscored the important role of mental imagery in contemporary cognitive behavioral therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst CBT is undoubtedly efficacious, treatment outcomes are not always satisfactory (Hudson et al, 2015;Westen and Morrison, 2001). Driven by the need to develop more effective cognitive behavioural interventions, experiential methods have recently experienced renewed interest (Borkovec et al, 2003;Saulsman et al, 2019). Of these, cognitive behavioural forms of chairwork are perhaps most enigmatic and poorly understood (Pugh, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that mental imagery can trigger a range of emotional responses, serving as an "emotional ampli er" (48) affecting motivation and behaviors. It makes imagery a powerful facilitator in bringing cognitive, affective, and behavioral change in positive way (49) enhancing the level of anticipated pleasure (50). It tends to evokes stronger subjective emotional responses, compared to those triggered by verbal processing patterns, in both physiological, neurological layer that tend to be stronger than those triggered by (13).…”
Section: Discussionmentioning
confidence: 99%